Exploring Business Opportunities in a Growing Local Food Market: A Strategic Planning Approach - Dermawan, Mahdi Raihan; Adi, Agung Nugroho (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to evaluate the feasibility and business prospects of establishing Warung Seblak Sundakita in Malang City by developing a comprehensive business plan to support sustainable growth in the increasingly competitive culinary industry. Design/Methodology/Approach – This study adopts a qualitative approach supported by library research. Data were collected through observations, interviews, and document analysis to assess key business aspects, including product development, marketing, operations, management, and business development strategies. The validity of the findings was ensured through the triangulation of multiple data sources. Findings – The analysis indicates that Warung Seblak Sundakita has strong potential to compete in the growing seblak market in Malang City. The proposed business plan emphasizes product development, effective marketing strategies, operational and managerial planning, as well as business development through product innovation and market expansion. These strategic initiatives provide a solid foundation for improving business competitiveness and achieving sustainable business growth. Originality/Value This research offers originality by developing a comprehensive business plan specifically for a seblak-focused culinary venture in a local urban market context. The findings provide practical value by presenting an integrated framework covering product innovation, marketing, operations, and managerial strategies to support sustainable business growth.